Krisis Identitas Agama pada Usia Remaja - Putri, Erita Riski (Bayani, 2023)
Adolescence is a period full of changes, both physical and psychosocial, resulting in dynamic changes in the way they view and think about themselves and the world. Changes that lead to cognitive maturity: this is a condition of anxiety that is often interpreted as a search for identity or an identity crisis, where this condition is a natural one for adolescents, and part of that search includes the search for forms of religious identity, which is the principle of human life. Many factors influence the crisis of religious identity in adolescents, as well as the need to identify the right dominant factor to use as a reference in the formation of a healthy religious identity.